Pengaruh Komposisi Media Tanam dan Pemberian Pupuk Anorganik Majemuk Terhadap Pertumbuhan Awal Bibit Kelapa Sawit (Elaeis guineensis Jacq.) - SIMANULLANG, ARJUNA YOHANNES; ARTHA, I NENGAH; SUWASTIKA, A. A. N. GEDE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.6, No.2, April 2017, 2017)
The Effect of Composition Planting Medium and Inorganic Compound Fertilizer application on The Growth of Early Oil Palm Seeds (Elaeis guineensis Jacq.) This study aims to: understand the interaction effect of composition planting medium and inorganic compound fertilizer application on the growth of early oil palm seeds (Elaeis guineensis Jacq). Research on the effect of composition planting medium and inorganic compound fertilizer using factorial randomized block design with two factors, namely: (planting medium, compost: soil: sand) which consists of four levels, namely: (0 compost: 1 soil: 1 sand), (1 compost: 1 soil: 1 sand), (2 compost: 1 soil: 1 sand), (3 compost: 1 soil: 1 sand), while the inorganic compound fertilizer application consists of three levels, namely: 0 g / polybag; 2.5 g / polybag; 5 g / polybag. Observations were made on plant height, stem diameter, leaf area, number of leaf chlorophyl, oven dry weight of shoots, roots oven dry weight, total dry weight of seedlings, shoot ratio, plant growth rate, and net assimilation rate. Data were analyzed by analysis of variance and if the real effect will be tested further with LSD 5%. The results of this study indicate that the interaction of composition planting media and inorganic compound fertilizers are not significant to the growth of early oil palm seeds (Elaeis guineensis Jacq). Single factor of planting medium and inorganic compound fertilizer is not significant to the growth of early oil palm seedlings (Elaies guineensis Jacq.). The highest value seen in the growing compost media composition: soil: sand (2: 1: 1), inorganic compound fertilizer highest value contained in a dose of 2.5 g / polybag on parameters of leaf area, leaf chlorophyll, dry root weight of the oven, and total weight of oven dried beans.